(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The manuscript Milan, Biblioteca Ambrosiana, R 61 sup. belong to the first unit of the S. Maria Incoronata Augustinian Library in Milan. Its bookbinding is made up of bare boards covered by half-skin and guard-leafs of reused parchments. On these parchments are scarcely legible the texts of twenty imbreviaturaewritten in Cremona for Giovannibuono de Giroldis from April to June 1260. These imbreviaturae belong to a little group of survival notarial registers of XIIIth century and they record a crucial period in the history of the Church and the city of Cremona.